Flexible Magnetoelectric Nanocomposites with Tunable Properties. (26th April 2016) - Alnassar, Mohammed Y.; Ivanov, Yurii P.; Kosel, Jürgen
Abstract : A flexible and transparent magnetoelectric nanocomposite is made of magnetostrictive galfenol nanowires and piezoelectric P(VDF‐TrFE) for magnetic energy conversion and harvesting applications. The large magnetostriction of galfenol nanowires enables superior magnetoelectric performance. A magnetic field treatment during sample fabrication aligns the nanowires embedded inside the polymer matrix, providing tunable, anisotropic properties.